Detection of Influenza and Other Respiratory Viruses in Air Sampled From a University Campus: A Longitudinal Study. (9th April 2019) - Xie, Chenyi; Lau, Eric H Y; Yoshida, Tomoyo; Yu, Han; Wang, Xin; Wu, Huitao; Wei, Jianjian; Cowling, Ben; Peiris, Malik; Li, Yuguo; Yen, Hui-Ling
Abstract: Background: Respiratory virus–laden particles are commonly detected in the exhaled breath of symptomatic patients or in air sampled from healthcare settings. However, the temporal relationship of detecting virus-laden particles at nonhealthcare locations vs surveillance data obtained by conventional means has not been fully assessed. Methods: From October 2016 to June 2018, air was sampled weekly from a university campus in Hong Kong. Viral genomes were detected and quantified by real-time reverse-transcription polymerase chain reaction. Logistic regression models were fitted to examine the adjusted odds ratios (aORs) of ecological and environmental factors associated with the detection of virus-laden airborne particles. Results: Influenza A (16.9% [117/694]) and influenza B (4.5% [31/694]) viruses were detected at higher frequencies in air than rhinovirus (2.2% [6/270]), respiratory syncytial virus (0.4% [1/270]), or human coronaviruses (0% [0/270]). Multivariate analyses showed that increased crowdedness (aOR, 2.3 [95% confidence interval CI, 1.5–3.8]; P < .001) and higher indoor temperature (aOR, 1.2 [95% CI, 1.1–1.3]; P < .001) were associated with detection of influenza airborne particles, but absolute humidity was not (aOR, 0.9 [95% CI, .7–1.1]; P = .213). Higher copies of influenza viral genome were detected from airborne particles >4 μm in spring and <1 μm in autumn. Influenza A(H3N2) and influenza B viruses that caused epidemics during the study period were detected in air prior to observing increased influenza activities in the community. Conclusions: Air sampling as a surveillance tool for monitoring influenza activity at public locations may provide early detection signals on influenza viruses that circulate in the community. Abstract : Influenza viruses were detected at higher frequencies than other respiratory viruses in air sampled from a university campus. Increased crowdedness and higher indoor temperature were associated with detection of influenza airborne particles by multivariate analyses.